Stimulant Activity of White Pepper (Piperis albi Fructus) Ethanol Extract In Vivo - Khaerunnisa, Arini; Jayantie, Dhyneu Dwi; Sutihat, Sutihat; Hida, Nurul; Suryani, Nani (Pharmacon: Jurnal Farmasi Indonesia, 2024)
Caffeine is a stimulant substances that can stimulate the central nervous system (CNS) increasing concentration, and reducing drowsiness. The use of caffeine generally comes from coffee plants which can increase gastrin secretion. Long-term use of caffeine can cause side effects such as feelings of anxiety, irritability, insomnia and faster heart rate. An alternative stimulant that has limited side effects is needed. White pepper (Piperis albi fructus) is potential as stimulant. The extract of White pepper contained piperine compound. Piperine can potentially be a stimulant because it can stimulate the formation of energy in the body. The purpose of this study was to determine the in vivo stimulant activity of ethanol extract White pepper in male white mice. The method used in this research is Natatory exhaustion. 25 test animals were divided into 5 groups. The doses used are white pepper extract 0.32; 0.65 and 1.3 mg/20 g BW, caffeine 0.26 mg/20 g BW and 0.5% CMC-Na. Data analysis with SPSS 16 with the Kruskal-Wallis test and the Mann-Withney test. The results of the stimulant activity test of white pepper ethanol extract at a dose of 0.32; 0.65 and 1.3 mg/20 g BW for male white mice with the DDY strain with an average % increase in stamina of 63.92; 120.81 and 179.31%,mean while in the positive control of caffeine by 232.55% and the negative control of CMC-Na by 21.10%. White pepper ethanol extract dose of 1.3 mg/20 g BW has stimulant activity which is not significantly different from caffeine positive control.